(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Robotics is where time-saving smart functioning is necessary, growing industries create innovative technologies that boost production. Robotics is a technology that concentrates on making humans’ lives more pleasant and automated. The purpose of this research is to examine the many uses of robotics to understand the relevance of robotics in organizations for lowering labor costs. Different professionals investigate the uses of robotics in industries through unique perspectives, which expands the reach of robotics in numerous sectors. Robots have a great impact on industries which makes them industries profitable and productive without the need for more labor. As a result, robotics has become a significant aspect of the business because machines conduct the majority of the job. Within the next several years, robots will encompass all of the major industrial areas where labor is used to lower labor costs for companies.